Effects of Product Differentiation Strategy and Pricing Strategy on the Performance of Manufacturing Firms in Nigeria - Mary O. OGUNDIPE; Oladele J. KEHINDE; Samuel E. OIKEH; Dorothy OYO-ITA (Communications of International Proceedings, 2020)
The new demand for modernization has made businesses perceive the globalization of their operations as a way of staying competitive. Globally, marketing strategy has been an effective resource for every company to survive in a competitive business environment and have become stronger. The major purpose of this research was to examine the effects of product differentiation strategy and pricing strategy on the performance of manufacturing firms in Nigeria. Product differentiation strategy and pricing strategy have been used as a tool for firm performance. The findings revealed that product differentiation strategy and pricing strategy has great influence on performance of manufacturing industry. This study therefore suggested that management must ensure that the contexts of their business environment are thoroughly examined, before any marketing strategy is adopted to determine whether the proposed step or decision is a suitable strategy for success in the sector.
Keywords: Marketing Strategies; Manufacturing Industry; Product Differentiation Strategy; Pricing strategy.